Penegakan Hukum Pidana Terhadap Penyalahgunaan Senjata Api Pasca Perdamaian Di Aceh : Studi Di Wilayah Hukum Kepolisian Resor Aceh Timur - Muhammad Iqbal Rozi; Syafruddin Kalo; Madiasa Ablisar; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
Abstract. The issue of the misuse of firearms in East Aceh after peace in Aceh is equally important for us to examine, namely regarding the issue of legal violations or criminal acts which after peace in Aceh there were many criminal acts of misuse of firearms, which occurred in several districts / cities in the province of Aceh, because many firearms left behind conflict or belonged to former combatants of the Free Aceh Movement who were still circulating freely in the midst of the community. Legal regulations governing the misuse of firearms, namely Law Number 8 of 1948 concerning Registration and Granting of Firearms Use Permits, Emergency Law Number 12 of 51 concerning Firearms, Perpu Number 20 of 1960, National Police Regulation Number 18 of 2015. Law enforcement carried out by the East Aceh Resort Police against perpetrators of firearms abuse starts from the stage of law enforcement at the level of investigation, the process of law enforcement at the level of investigation, the process of arrest, prosecution and enforcement processes in the trial. The constraints faced by the East Aceh police are weak supervision, lack of information from the community, constraints on the legal structure and legal culture of the community. While the efforts made by the East Aceh Resort Police to combat post-peace firearms abuse in Aceh were the first internal factors, among others, efforts to improve cooperation to obtain information, efforts to overcome human resource constraints, efforts to overcome legislative obstacles. The second external factor attempts to overcome the lack of community roles and efforts to overcome geographical constraints. Keywords: Criminal Law Enforcement, Abuse of Firearms in East Aceh